Green Marketing, Consumer Perception, and Environmental Awareness on Sustainable Purchase Intention - Endang Sungkawati; Klemens Mere; Nova Dwi Hernanik; Dian Rokhmawati (goodwood publishing, 2026)
Purpose: This study examines the relationship between consumer perception, environmental awareness, and sustainable purchase intention, with a green marketing strategy as a mediating variable. It also addresses the limited empirical evidence on green marketing implementation in tourism-based MSMEs. Research Methodology: This study applies a quantitative explanatory approach. Data were collected using questionnaires from 150 visitors across nine tourism villages in Malang, East Java, Indonesia. Path analysis was used to test both direct and indirect relationships between the variables. Results: The results show that consumer perception, environmental awareness, and green marketing strategies have positive and significant effects on sustainable purchase intention. Green marketing strategies also mediate the relationship between consumer perception, environmental awareness, and purchase intention. Consumers show a stronger intention to purchase MSME products that emphasize eco-friendly packaging, natural materials, and clear sustainability messages. Conclusions: Green marketing strategies play a critical role in strengthening sustainable purchase intentions when supported by positive consumer perceptions and environmental awareness. Limitations: This study is limited to tourism villages in one region and focuses only on tourist respondents. Contributions: This study provides empirical evidence of the mediating role of green marketing strategies in tourism village MSMEs. It offers practical insights for MSME actors and local stakeholders to design more effective sustainability-oriented marketing strategies.